Developmental Programming of Obesity and Liver Metabolism by Maternal Perinatal Nutrition Involves the Melanocortin System - Cordero, Paul; Li, Jiawei; Nguyen, Vi; Pombo, Joaquim; Maicas, Nuria; Novelli, Marco; Taylor, Paul D; Samuelsson, Anne-Maj; Vinciguerra, Manlio; Oben, Jude A (Nutrients, 2017)
Maternal obesity predisposes offspring to metabolic dysfunction and Non-Alcoholic Fatty Liver Disease (NAFLD). Melanocortin-4 receptor (Mc4r)-deficient mouse models exhibit obesity during adulthood. Here, we aim to determine the influence of the Mc4r gene on the liver of mice subjected to perinatal diet-induced obesity. Female mice heterozygous for Mc4r fed an obesogenic or a control diet for 5 weeks were mated with heterozygous males, with the same diet continued throughout pregnancy and lactation, generating four offspring groups: control wild type (C_wt), control knockout (C_KO), obese wild type (Ob_wt), and obese knockout (Ob_KO). At 21 days, offspring were genotyped, weaned onto a control diet, and sacrificed at 6 months old. Offspring phenotypic characteristics, plasma biochemical profile, liver histology, and hepatic gene expression were analyzed. Mc4r_ko offspring showed higher body, liver and adipose tissue weights respect to the wild type animals. Histological examination showed mild hepatic steatosis in offspring group C_KO. The expression of hepatic genes involved in regulating inflammation, fibrosis, and immune cell infiltration were upregulated by the absence of the Mc4r gene. These results demonstrate that maternal obesogenic feeding during the perinatal period programs offspring obesity development with involvement of the Mc4r system.
Keywords: Liver; játra; Maternal Nutritional Physiological Phenomena; Triglycerides; receptor melanokortinový typ 4; Obesity; krevní glukóza; Perinatal Care; těhotenství; alanintransaminasa; perinatální péče; Non-Alcoholic Fatty Liver Disease; Gene Expression Regulation; developmental programming; Disease Models, Animal; obesity; Mice; Mice, Obese; Alanine Transaminase; myši knockoutované; regulace genové exprese; Blood Glucose; modely nemocí na zvířatech; aspartátaminotransferasy; ženské pohlaví; zvířata; Aspartate Aminotransferases; Pregnancy; intra-abdominal fat; zpožděný efekt prenatální expozice; Receptor, Melanocortin, Type 4; triglyceridy; Mice, Knockout; myši; obezita; maternal nutrition; Female; fyziologie výživy v mateřství; Prenatal Exposure Delayed Effects; myši obézní; Animals